1997
DOI: 10.1093/oxfordjournals.aje.a009349
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Invasive Cancers Following Squamous Cell Skin Cancer

Abstract: The authors describe the incidence of new primary cancers among 4,639 cases of squamous cell skin cancer (SCC) diagnosed between 1974 and 1994 in the cancer registries of the Swiss cantons of Vaud and Neuchatel (total person-years at risk = 23,152). Overall, 729 metachronous cancers were observed versus 527.6 expected, corresponding to a standardized incidence ratio (SIR) of 1.4 (95% confidence interval (Cl) 1.3-1.5). After exclusion of skin cancers, however, 384 second primary neoplasms were observed versus 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
62
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 24 publications
8
62
0
2
Order By: Relevance
“…In contrast to the scarcity of familial data on skin SCC, there are many studies published on second cancers following skin SCC (Frisch and Melbye, 1995;Levi et al, 1996Levi et al, , 1997Levi et al, , 1998Wassberg et al, 1999;Dong and Hemminki, 2001b;Hemminki and Dong, 2000b, c;Milan et al, 2000). These have shown a consistent link between SCC and melanoma, while an association between skin and eye cancer has been noted (Milan et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the scarcity of familial data on skin SCC, there are many studies published on second cancers following skin SCC (Frisch and Melbye, 1995;Levi et al, 1996Levi et al, , 1997Levi et al, , 1998Wassberg et al, 1999;Dong and Hemminki, 2001b;Hemminki and Dong, 2000b, c;Milan et al, 2000). These have shown a consistent link between SCC and melanoma, while an association between skin and eye cancer has been noted (Milan et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Other dominant risk factors are smoking and immunosuppression. A number of studies have found significantly increased risks of various second primary cancers in SCC patients Levi et al, 1997;Wassberg et al, 1999;Askling et al, 1999;Hemminki and Dong, 2000;Hemminki et al, 2001;Efird et al, 2002). Some general patterns can be seen from these studies.…”
mentioning
confidence: 86%
“…Patients with melanoma are known to be at a substantially increased risk of the nonmelanoma skin cancers (NMSC) BCC and SCC (Wassberg et al, 1996;Levi et al, 1997a;Hemminki et al, 2003;Crocetti and Carli, 2004) and the converse is also true (Levi et al, 1997b(Levi et al, , 1998Wassberg et al, 1999;Bower et al, 2000;Maitra et al, 2005). However, it is not known whether the association between melanoma and NMSC varies according to the anatomical site.…”
mentioning
confidence: 99%